Vertical aerosol distribution in the southern hemispheric midlatitudes as observed with lidar in Punta Arenas, Chile (53.2° S and 70.9° W), during ALPACA - Foth, Andreas; Kanitz, Thomas; Engelmann, Ronny; Baars, Holger; Radenz, Martin; Seifert, Patric; Barja Gonzalez, Boris; Fromm, Michael; Kalesse, Heike; Ansmann, Albert (My University, 2019)
Within this publication, lidar observations of the vertical aerosol distribution above Punta Arenas, Chile (53.2 degrees S and 70.9 degrees W), which have been performed with the Raman lidar Polly(XT) from December 2009 to April 2010, are presented. Pristine marine aerosol conditions related to the prevailing westerly circulation dominated the measurements. Lofted aerosol layers could only be observed eight times during the whole measurement period. Two case studies are presented showing long-range transport of smoke from biomass burning in Australia and regionally transported dust from the Patagonian Desert, respectively. The aerosol sources are identified by trajectory analyses with the Hybrid Single-Particle Lagrangian Integrated Trajectory (HYS-PLIT) and FLEXible PARTicle dispersion model (FLEX-PART). However, seven of the eight analysed cases with lofted layers show an aerosol optical thickness of less than 0.05. From the lidar observations, a mean planetary boundary layer (PBL) top height of 1150 +/- 350 m was determined. An analysis of particle backscatter coefficients confirms that the majority of the aerosol is attributed to the PBL, while the free troposphere is characterized by a very low background aerosol concentration. The ground-based lidar observations at 532 and 1064 nm are supplemented by the Aerosol Robotic Network (AERONET) Sun photometers and the space-borne Cloud-Aerosol Lidar with Orthogonal Polarization (CALIOP) aboard the Cloud-Aerosol Lidar and Infrared Pathfinder Satellite Observation (CALIPSO). The averaged aerosol optical thickness (AOT) determined by CALIOP was 0.02 +/- 0.01 in Punta Arenas from 2009 to 2010.
Keywords: HYSPLIT; AERONET; Sun photometer